Stac na Cuibhig (Scottish Historical and Archaeological Internet Reports, 2009)
This chapter presents a physical description, details of location, extent of erosion, method of access and previous work. Although Stac na Cuibhig has been the site of human activity culminating in a structure there is not enough evidence to adequately support any further interpretation.